ANALISIS KEMAMPUAN BERINOVASI WIRAUSAHAWAN MUDA PADA PROGRAM PENUMBUHAN WIRAUSAHAWAN MUDA PERTANIAN (PWMP) DI WILAYAH SUMATERA - Kansrini, Yuliana; Lubis, Zulkarnain; Effendi, Ihsan; Mulyani, Puji Wahyu; Putra, Yunanda Eka (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2025)
ABSTRACTThe implementation of the Program for Growing Young Agricultural Entrepreneurs (PWMP) has been carried out by Vocational Higher Education within the Ministry of Agriculture, with one of the implementing institutions is the Politeknik Pembangunan Pertanian Medan in the Sumatra region. The ability to innovate is a crucial factor in business development and sustainability. This study aims to identify and analyze the innovative capabilities of young entrepreneurs participating in the PWMP Program in the Sumatra region. This study employs a quantitative descriptive research method to assess young entrepreneurs' ability to innovate. The population consists of PWMP Program participants from 2020 to 2023, totaling 142 respondents. The sampling technique used in this study is the saturated sampling method, in which all PWMP participants are included as samples. Quantitative data are measured using a Likert scale and interpreted within respective categories. Based on the study results, the ability to innovate among PWMP Program entrepreneurs in the Sumatra region falls into the low category, at 45.70 percent. The lowest ability is observed in the dimension of organizational innovation development (40.23%), particularly in creating management strategies and ensuring effective administration. Conversely, the highest ability is found in the dimension of product innovation development (50.09%), especially in identifying product needs. PWMP Program participants should be selected based on their ability to innovate, with an emphasis on business management skills, including the generation of innovative ideas to enhance the competitiveness of agricultural businesses in the digital era. The successful implementation of the PWMP Program also requires coaching to strengthen young entrepreneurs' innovative capabilities through the use of the latest technology, thereby improving productivity and efficiency.